High-performance heterogeneous computing - Lastovetsky, Alexey, 1957- (Wiley, 2009)
An analytical overview of the state of the art, open problems, and future trends in heterogeneous parallel and distributed computing. This book provides an overview of the ongoing academic research, development, and uses of heterogeneous parallel and distributed computing in the context of scientific computing. Presenting the state of the art in this challenging and rapidly evolving area, the book is organized in five distinct parts:. Heterogeneous Platforms: Taxonomy, Typical Uses, and Programming Issues;. Performance Models of Heterogeneous Platforms and Design of?Heterogeneous Algorithms.